Communication in the Digital World - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
The aim of this chapter is to give a short review about the main caracteristics of online communication focusing on the minors. The iGeneration prefer the ‘computer-mediated communication’ (CMC) or ‘mobile-mediated communication’ (MMC) versus face-to-face communication.The online communication has different forms and platforms, which are depend from the age of users. The online communication has a lot of positive elements, but very important risk-factors which are not or only to a limited extent recognized by the younger (and of course other) generations.Keywords: online communication, iGeneration, FTF vs M2M communication, risk-factors